Guidance and tutoring university: current approximation - Clemente Lobato Fraile; Maria Celia Ilvento (Universitat Politècnica de València, 2013)
Since the beginning of this century, University has been experiencing a profound transformation. In this framework, the guidance and tutoring are a major issue in Higher Education. The modern Life designing conception highlights two fundamental factors: the commitment of the person in the construction of the life-project through systematic reflection and the need for professional support in different forms and contexts: a challenge for reflection and creative response of guidance and mentoring at universities. This is why innovations in tutoring are so numerous, promoted at universities either by teachers or by governance in order to achieve the implementation of guidance and tutoring systems, based on new technologies and scientific developments that respond to identified needs. This is generating an innovative dynamics and a structural renovation at universities, achieving a better Higher Education quality. Thus, the studies included in this paper constitute a mosaic of intervention practices in University.